We are the Lambeth Boys - Reisz, Karel; Lassally, Walter (Duke Video, 2009)
"We are the Lambeth Boys" is a fascinating glimpse into the everyday lives of working class young people in the Britain of the 1950s. This pioneering documentary - part of the Free Cinema movement - was one of the first films to give this section of the community a voice, and remains an important and ground-breaking work. Made for the Ford Motor Company's "Look at Britain" series, "We are the Lambeth Boys" was directed by Karel Reisz, who would go on to direct critically-acclaimed feature films such as "Saturday Night Sunday Morning" and the award-winning "The French Lieutenant's Woman". His 'fly-on-the-wall' style allowed his subjects to speak for themselves, revealing their hopes and fears, their loves and hates as a revolution in youth culture offered new opportunities, and new challenges. [www.dukevideo.com]